Role of the bedouins in the national revolution in Egypt in 1882 - V. V. Romanov; S. A. Bogomolov (Nomadic Civilization: Historical Research, 2022)
The article analyzes the role of the Bedouins in the general revolution of 1882 in Egypt. In 1882, British troops occupied Egypt, incorporating it into the British Empire. Features of the economic and cultural type of the peoples of Egypt primarily depend on the natural and climatic conditions of the habitat. Among the population were nomadic shepherds who raised cattle. The Bedouins in Egypt are part of the country’s indigenous population, leading a nomadic lifestyle. The word Bedouin itself is translated from Arabic as “desert dweller” and is contrasted with the word khadir “settled person”.Opposing political forces tried to attract nomads to their side, but they always took an independent position, maintaining a hostile attitude towards urban civilization. Nomadic militias joined the Egyptian army in resisting British intervention. At the same time, the Bedouins protected friendly Christians during massacres, looted Muslims in the suburbs, and sold cattle to the British quartermasters. During the British occupation, nomadic societies gradually integrated into the new market economy as pastoralists and service personnel for European tourists. The use of the even-analysis method allowed the authors to organize and structure the information in the form of an event series.